Lattice defects in quinacridone. Issue 5 (8th September 2022) - Brey, Dominik; Scherer, Barbara; Schmidt, Martin U.
Abstract : Various lattice defects in the α I ‐phase of quinacridone (C20 H12 N2 O2 ) were simulated using lattice‐energy minimizations, including vacancies, stacking faults, screw and edge dislocations, twinning and orientational faults. Twinning and orientational faults of entire chains were calculated to occur most frequently. Abstract : Various lattice defects in the α I ‐phase of quinacridone (C20 H12 N2 O2 ) were simulated using lattice‐energy minimizations. α I ‐Quinacridone forms a chain structure in P 1, Z = 1. The molecules are connected by hydrogen bonds along [010], by π‐stacking along [100] and by weak van der Waals interactions along [001]. α I ‐Quinacridone is inherently nanocrystalline. Lattice defects were calculated in correspondingly large supercells with up to 4464 atoms, using a previously evaluated force field. Vacancies, vacancy aggregates and interstitial molecules are energetically very unfavourable. A misorientation of a single molecule (flip around [010] by 180°) causes an energy increase of 243.7 kJ mol −1 . Various edge and screw dislocations were investigated. A screw dislocation along [010] causes an energy increase of Δ E = 38.0 kJ mol −1 per molecule, all other line dislocations are even worse. In contrast, the rotation of an entire chain around the chain axis [010] by 180° leads to only a very small energy increase (Δ E = 1.6 kJ mol −1 ) and the real crystals probably contain a high number of such defects. Various planar defects were calculated, including different stacking disorders and misfit‐layer structures with two different types of layers having different lateral periodicities. Stacking faults along [001] with herringbone stacking instead of parallel stacking are energetically quite favourable (Δ E = 2.2 kJ mol −1 ); the same is true for domains with misoriented molecules in the [001] direction. As an example for a bulk defect, domains are calculated in which blocks of 4 × 4 chains are rotated by 180° around [010], which leads to an energy increase of only 1.1 kJ mol −1 . Twinning by mirroring at the (001) plane is energetically favourable (Δ E = 0.9 kJ mol −1 ). This twinning was observed in an HRTEM image. It is probable that the crystallites also contain rotations of chains, layers or blocks around [010] by 180°, but these defects cause only a very slight modification of the molecular packing, which was not observable in the HRTEM image. The lattice defects in α I ‐quinacridone investigated here provide an insight into lattice defects, their energies and local structures. Similar lattice defects are expected to occur also in other similar organic chain structures.